Trends on the Brazilian research in physical education: part 1: a view through national journals - Rosa, Suely; Leta, Jacqueline (Brazilian journal of physical education and sport, 2010)
After few centuries of its foundation, the discipline of Physical Education (PE) resides with a dichotomic approach: on the one hand, the tradition of its medical and biological aspects and on the other hand, socio-cultural, political and philosophical issues are highlighted. This seems to disrupt the historical concept of "the biologized body". Within this context, we have started an investigation of trends in Brazilian research on PE. Using a bibliometric approach, in the present paper we analyze scientific publications from four Portuguese-language journals, in the 2001-2005 period. Our aim is identify with of the two concepts prevail in Brazilian current research on EP. The following steps were taken: a) data-gathering and categorization; and b) quantitative and qualitative analyses. We found that 431 (72.43%) out of 595 of the publications analyzed were from the biological sciences. More specifically, 376 (63.19%) were from physiology. These results point to the prevalence of a broad biological approach to PE, in which anatomical, biochemical, biophysical, and medical aspects at large are prevalent. Although our data does not allow us to give a complete picture of research trends in PE in Brazil, they suggest that PE's current research in the country is still biologically-oriented, revealing its strong historical concept.